Practical Django Projects - Bennett, James; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
Build a Django content management system, blog, and social networking site with James Bennett as he introduces the popular Django framework. You'll work through the development of each project, implementing and running the applications while learning new features along the way. Web frameworks are playing a major role in the creation of today's most compelling web applications, because they automate many of the tedious tasks, allowing developers to instead focus on providing users with creative and powerful features. Python developers have been particularly fortunate in this area, having been able to take advantage of Django, a very popular open source web framework whose stated goal is to “make it easier to build better web applications more quickly with less code.” Practical Django Projects is the first book to introduce this popular framework by way of a series of real–world projects.
Welcome to Django -- Your First Django Site: A Simple CMS -- Customizing the Simple CMS -- A Django-Powered Weblog -- Expanding the Weblog -- Templates for the Weblog -- Finishing the Weblog -- A Social Code-Sharing Site -- Form Processing in the Code-Sharing Application -- Finishing the Code-Sharing Application -- Writing Reusable Django Applications.
Keywords: Software engineering; Software Engineering/Programming and Operating Systems